Dissidence comique et belliqueuse : influence rabelaisienne dans les pamphlets du début du xviie siècle - Dorothée Lintner (Les Dossiers du GRIHL)
The article highlights Rabelais’s reception as a dissident author: in the 17th century, not only has he been misjudged as many critics have emphasized it (Lazare Sainéan, Jacques Boulenger), but also felt to be warlike. The article refers to Garasse’s famous attacks, but also to the anonymous pamphlets written during Louis XIII’s reign (le Nouveau Panurge, la Harangue du Capitaine Picotin, l’Anti-Thersite ou la Response à Maître Guillaume), so as to show the ambiguous mechanism of the dissident portrait these texts brushes: Rabelais and his character Panurge face often criticism because of their fierce effrontery, that is more perceived as dangerous than naïve and ridiculous. Paradoxically, by being pamphleeters’s targets, these comic figures both support the pamphleeters’ cause, in the end.